2017
DOI: 10.1111/jnc.14216
|View full text |Cite
|
Sign up to set email alerts
|

Functional changes in the neural retina occur in the absence of mitochondrial dysfunction in a rodent model of diabetic retinopathy

Abstract: Diabetic retinopathy is a neurovascular diabetes complication resulting in vision loss. A wealth of literature reports retinal molecular changes indicative of neural deficits, inflammation, and vascular leakage with chronic diabetes, but the mechanistic causes of disease initiation and progression are unknown. Microvascular mitochondrial DNA (mtDNA) damage leading to mitochondrial dysfunction has been proposed to drive vascular dysfunction in retinopathy. However, growing evidence suggests that neural retina d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 48 publications
(73 reference statements)
0
18
0
Order By: Relevance
“…Absolute copy number of mitochondrial DNA (mtDNA) was quantified (copies per ng input DNA) by digital PCR based on a previously reported method …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Absolute copy number of mitochondrial DNA (mtDNA) was quantified (copies per ng input DNA) by digital PCR based on a previously reported method …”
Section: Methodsmentioning
confidence: 99%
“…39 Determination of mitochondrial DNA copy number Absolute copy number of mitochondrial DNA (mtDNA) was quantified (copies per ng input DNA) by digital PCR based on a previously reported method. 40,41 Immunoblot and qPCR Standard procedures were used for western blots and qPCR. Antibodies and primers used are detailed in Table S2.…”
Section: Quantification Of Protein Abundances By Selected Reaction Momentioning
confidence: 99%
“…Prior to the intravitreal cytokine injection, we conducted baseline assessments of both non-diabetic CD1 and diabetic NOD mice with CD1 mice being significantly larger and heavier than the NOD mice. This weight difference is not surprising as it has previously been reported that diabetic mice, particularly with type 1 diabetes, tend to weigh less than their non-diabetic controls due to their metabolic imbalance [ 25 ]. It is noteworthy that CD1 mice, the genetic background strain for NOD mice, showed higher blood glucose levels than expected.…”
Section: Discussionmentioning
confidence: 62%
“…These findings raise the important question of whether, in diabetes, the retina exhibits a “metabolic switch” towards increased FA oxidation, similar to other high-energy consuming organs (e.g., heart, kidney). While such data are scarce, at least one study has indicated that the retina can increase the expression of FA oxidation enzymes in diabetic rats [ 100 ]. Subsequent studies will be needed, however, to characterize and quantify the relative contribution of individual energetic substrates to energy production in the diabetic retina.…”
Section: Retinal Bioenergetics and Mitochondrial Substrate Selectimentioning
confidence: 99%